Multi display scan in detecting weld discontinuity of thick carbon steel plate using ultrasonic testing phased array (UTPA) with comparison to conventional ultrasonic testing (UT) / Jeffry Jamil, Syed Yusainee Syed Yahya and Rosnah Zakaria - Jamil, Jeffry; Syed Yahya, Syed Yusainee; Zakaria, Rosnah (Universiti Teknologi MARA Shah Alam, 2020)
Non-destructive testing (NDT) is a method of testing and analysis that relies on the application of physical principles to determine the integrity of materials without causing damage. The existence of weld discontinuity can affect the service ability of the structures. Ultrasonic testing Phases Array (UTPA) is advanced ultrasonic testing technology widely practiced in many industries. The multiple ultrasonic elements and electronic time delay will create constructive and destructive interference and steering capability, which could improve detectability compared to a single element of conventional UT. The multi displays presented in A-Scan, S-scan, B-Scan, and C-Scan of UTPA equipment capable of locating, inspecting, and characterise defects within the welded component. Two carbon steel plates with thickness 18 mm and 24 mm were prepared and cut to V-shape configuration and welded using shielded metal arc welding (SMAW) process, labelled as NDE-8826 and NDE-8827 respectively. Both samples were induced with artificial defects of the weld. 16 elements of phased array probe with 0.5 mm pitch and 4 MHz were carried out for this study with encoded scanning to identify weld discontinuity plotted in different types of UT displays. Additional testing was performed using conventional ultrasonic testing (UT) using a 4 MHz probe to compare with the UTPA results and the acceptability of each defect detections. The length and datum of toe crack, slag, and lack of inter run fusion detected by UTPA in NDE-8826 give the same value as the actual value. However, the localisation of the defect is slightly different at 1.0 mm for UT detection. While the detection value for slag gives the same values for UT and UTPA, which also the same as the actual values. The detection of lack of penetration and lack of fusion in sample NDE-8827 was precisely can be detected by UT and UTPA; hence their datum value has slightly different in the centerline crack and porosity at 2.0 mm for UT measurement, and as for UTPA, it was found that the porosity at 3.0 mm which higher value compared to the actual value, 250 mm. From the result, a relevant indication from the UTPA and conventional UT collected it was found that the UTPA technique is capable of improving the Probability of Detection (POD) of defects compared to the conventional UT.